Testing a Model of Sodium Reduction in Hypertensive Older Thai Adults. Issue 1 (2nd January 2017) - Srikan, Pratsani; Callen, Bonnie; Phillips, Kenneth; Tavakoli, Abbas; Brockett, Ralph; Hanucharurnkul, Somchit; Beebe, Lora
ABSTRACT: Hypertensive older adults will benefit if there is a clear understanding of the factors related to sodium reduction. That would raise awareness of the causes, consequently reducing many health risks, lowering health care costs, and diminishing economic and social burden from high blood pressure. This study explored predictors of urinary sodium excretion. A cross-sectional, correlational study was conducted in 312 hypertensive older Thai adults. Questionnaires related to knowledge, self-care agency, self-care behavior of sodium reduction, and 24-hour urinary sodium analyses were used, followed by the application of structural equation modeling and the Analysis of Moment Structures program. Self-care agency, knowledge, self-care behavior, rural/urban location, and education accounted for 61% of urinary sodium excretion. Self-care agency, knowledge, and self-care behavior were the main predictors in the urinary sodium excretion model. This study suggests establishing supportive educative sodium reduction-related programs that improve knowledge and enhance self-care agency, as well as a comparison of the changes of sodium reduction self-care behavior and urinary sodium excretion over time after the intervention.